Some aspects of the denudation of the chalk in the County of Wiltshire - Green, C (1965)
﻿ The concern of the investigation described in this thesis has been to examine certain drift deposits in southern Wiltshire and to consider their distribution in relation to the accepted interpretation of the landscape. The area examined has been discussed by Wooldridge and Linton (1955) but lies on the periphery of the tract with which they deal, and their treatment is essentially theoretical and not circumstantial. In the course of the investigations which are described, samples were collected from over two hundred sites, surface indications of the geology were examined at a substantially larger number of sites and more than thirty sections were specially excavated in particularly interesting locations. The work is based not on the application of refined geological techniques but on the ability to distinguish, in hand specimens, common and distinctive rocks. In important sections, samples of gravel of from 6 lbs to 2O lbs weight were secured and broken down into three fractions (1⁄16"-5⁄32"; 5⁄32"-1⁄2"; 1⁄2" upwards); for correlative purposes exact counts of the component materials were carried out for the two coarser fractions. Although some of the individual examples encountered are problematic the conclusions have invariably been based on a significant volume of unmistakable material. The use of refined correlative techniques to confirm the results has not been attempted. This omission to some extent reflects the nature of the investigation, which is best regarded as a reconnaissance of a large area, describing evidence not only in Wiltshire but on the Chalk and Eocene outcrops elsewhere in We ss ex, for the most part on ground lying to the West of the Salisbury Avon. The results of the work are described in a comparative study of landscape features using, so far as possible, the whole geographical context of the ground examined: the dissection and weathering of the surface, the drifts and soils which rest upon it, and the relation of the ground to relief both above and below it. In Part One of the thesis an attempt is made to establish the nature of the sub-Eocene unconformity. A study of the Pleistocene river gravels about Salisbury suggests that Eocene formations may have been preserved on the western part of Salisbury Plain at the beginning of the Pleistocene period. This result is inconsistent with the views adopted by Wooldridge and Linton. The composition of the gravels examined suggests that the Eocene formations in question did not resemble formations now recognised in the main Eocene outcrops adjoining Salisbury Plain. A study of the Palaeogene outlier on Salisbury Plain, at Clay Pit Hill, shows the gravels in the outlier to be closely similar in terms of petrology to the distinctive gravels in the Bagshot Beds about Dorchester in Dorset, and a correlation with these beds is suggested. A distinctive gravel from another Palaeogene outlier, at Cley Hill, near Warrninster, is described. This gravel at a height of about 800' O.D. appears to be preserved at or near the level of its original deposition, and is tentatively referred to the Oligocene period. The evidence at Cley Hill and Clay Pit Hill is taken to show that the Chalk suffered extensive erosion during the Eocene and Oligocene periods. A study of sites on the ground intervening between the Palaeogene outliers on Salisbury Plain and the Bagshot outcrop in Dorset provides new evidence on the nature of the Reading Beds, which tends to confirm the results of the investigations on Salisbury Plain. In Part Two of the thesis drifts on the mid- Tertiary surface of Wooldridge and Linton (1955) are described. Drifts on the Upper Greensand outcrop in the Vales of Wardour and Warminster are believed to be of periglacial origin and Pleistocene age. Drift on the Portland outcrop in the Vale of Wardour appears to be the debris of Lower Cretaceous formations and probably rests on an intra-Cretaceous surface. On the Chalk a contrast is discerned between ground occupied by deep very flinty drifts of residual aspect and ground occupied by shallower flint drifts, also of residual aspect. The shallow drifts are shown to be associated with the relics of gravels incorporating Upper Greensand, Lower Cretaceous and Jurassic debris. The deep very flinty drifts are believed to confirm the views of Wooldridge and Linton concerning the mid-Tertiary surface, but the shallower drifts and associated gravels are thought to rest on a separate surface, and the Cretaceous and Jurassic debris is believed to imply the competence of transverse gradients during the dissection of the mid-Tertiary surface. The evidence described in Part Two of the thesis is difficult to reconcile with the concept of marine transgression across the Wiltshire Chalk. In Part Three of the thesis drifts on the supposed marine plain are described and the marine origin of the surface is rejected. Specific evidence of a 'Pliocene' transgression in Wessex is reviewed and a study of supposed 'Pliocene' material refers the material in question to the Eocene period. Problematic aspects of Pliocene stratigraphy and the concept of superimposition from a Pliocene surface are reviewed. Pinchemel's objections (1954) to a depositional surface are accepted but his views on fluvial aggradation are rejected in a study of gravel at Alderbury, near Salisbury, referred by him to this aggradation. Difficulties inherent in the concept of marine planation are recognised and ground referred by Wooldridge and Linton to the Pliocene marine plain is shown to be essentially indistinguishable from their mid-Tertiary surface and is therefore believed to be correlative with it. This view implies post-mid-Tertiary deformation of the Chalk. In Part Four of the thesis a theory of drainage evolution is developed to replace the hypothesis based on a concept of late Tertiary marine planation. Drifts, landforms and drainage morphology in the Vale of Wardour are shown to demonstrate a deformed, subaerial planation surface, bevelling the outcrop of the Chalk and earlier formations at a level below the mid-Tertiary surface of Wooldridge and Linton. The present drainage pattern is believed to have originated during the deformation of this surface, probably in the Plio-Pleistocene interval. This subaerial surface is also identified on Salisbury Plain and the origin of the drainage pattern there and in the Alderbury syncline is described. The available evidence suggests that the subaerial surface was elaborated during the Pliocene period following the deformation of the Oligo-Miocene (mid-Tertiary) surface. The character of the late Tertiary (Pliocene) surface suggests comparisons with the surfaces described by King (1962) and termed by him pediplains, although the nature of the process involved remains doubtful. In Part Five of the thesis some aspects of Pleistocene erosion are treated. Adjustments to the drainage pattern in the basin of the Avon above Salisbury during the Pleistocene period are discussed. This account is based on analyses of gravels of the Avon and its tributaries about Salisbury. The concept of successive stages of marine planation in the Hampshire Basin daring the Pleistocene period is rejected in a study of the composition and morphology of the Pleistocene gravels. An alternative scheme of subaerial planation is suggested and some morphological evidence of this planation on the Wiltshire Chalk and on the Eocene outcrop in the Hampshire Basin is described. The problems of scarp recession and the dessication of the dry valleys are reviewed and the concept of scarp recession is abandoned.. The Chalk escarpments are believed to have evolved where they now stand; the bearing of this idea on the dessication of the dry valleys is discussed. Evidence of the catastrophic nature of Pleistocene erosion is described and a concept of a 'clinatic cycle' reflecting Pleistocene glacial fluctuations is tentatively suggested. In the conclusion to the thesis it is stressed that the main importance of the work should be recognised not in the chronological treatments of the results but in the evidence that some of the fundamental concepts which have guided geomorphological research in southern England have in the past been applied without a proper recognition of the complications which may impair their value.